2022
DOI: 10.1002/anbr.202200093
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Manganese Dioxide‐Based Nanomaterials for Biomedical Applications

Abstract: Advancements in nanotechnology have promoted the rapid development of diverse nanosystems for biomedical applications. Manganese dioxide (MnO2) nanomaterials have attracted numerous attentions in the field of biosensing and cancer treatment due to their unique properties, such as simple fabrication procedures, broad optical absorption, and high oxidation and catalytic ability. Especially, the intelligent stimuli‐responsiveness of MnO2 nanomaterials to tumor microenvironment (TME) greatly improves their perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 178 publications
0
5
0
Order By: Relevance
“…BSA nanoparticles were chosen as the base for the nanoplatform due to their excellent biocompatibility and biodegradability as well as their naturally high affinity for binding both hydrophilic and hydrophobic molecules [27]. BSA solutions have also often been used for simultaneous reduction and stabilization in the synthesis of MnO 2 nanoparticles and nanodots [28][29][30]. However, not much is known about the use of BSA nanoparticles as biotemplates for preparation of MnO 2 core shell nanoparticles.…”
Section: Synthesis and Characterization Of Bam Npsmentioning
confidence: 99%
“…BSA nanoparticles were chosen as the base for the nanoplatform due to their excellent biocompatibility and biodegradability as well as their naturally high affinity for binding both hydrophilic and hydrophobic molecules [27]. BSA solutions have also often been used for simultaneous reduction and stabilization in the synthesis of MnO 2 nanoparticles and nanodots [28][29][30]. However, not much is known about the use of BSA nanoparticles as biotemplates for preparation of MnO 2 core shell nanoparticles.…”
Section: Synthesis and Characterization Of Bam Npsmentioning
confidence: 99%
“…Various MnO 2 -based diagnosis and treatment platforms have been explored for tumor imaging and treatment. 127 The physical and chemical properties of MnO 2 have also been shown to offer great advantages in the treatment of bone-related diseases, cardiovascular diseases and nervous system diseases (Table 3). In vivo and in vitro experiments in different animal models have shown that loaded, modified or doped MnO 2 nanomaterials can significantly increase the efficacy of nanotherapy.…”
Section: Mno 2 -Based Nanomaterials For the Treatment Of Other Diseasesmentioning
confidence: 99%
“…Functional MnO 2 nanoplatforms have attracted great interest due to their responsiveness to the TME and their ability to scavenge ROS. Various MnO 2 -based diagnosis and treatment platforms have been explored for tumor imaging and treatment . The physical and chemical properties of MnO 2 have also been shown to offer great advantages in the treatment of bone-related diseases, cardiovascular diseases and nervous system diseases (Table ).…”
Section: Mno2-based Nanomaterials For the Treatment Of Other Diseasesmentioning
confidence: 99%
“…MnJ showed good adjuvant effects for all tested antigens, including T cell-dependent and T cell-independent antigens [ 188 ]. However, despite MnO 2 nanomaterials having a great potential in the field of biomedicine, a strict biosafety assessment of MnO 2 -based nanosystems is needed in order to comprehensively determine the potential toxicity of Mn-based nanomaterials [ 189 , 190 , 191 ].…”
Section: To the Metals!mentioning
confidence: 99%